PEMANFAATAN KULIT RAMBUTAN (Nephelium lappaceum) SEBAGAI ADSORBEN LOGAM TIMBAL (Pb) - Alissa Putri Almuchty (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2020)
Present of lead as a heavy metal can be harmful to health. One possible method to reduce the presence of lead metal content is obtained through the adsorption process using adsorbent from rambutan rind. This study aimed to determine the effectiveness of activated charcoal from rambutan rind in absorbing lead metal with variations of difference adsorbent mass and stirring time. In this study, chemical activation was carried out by soaking the rambutan rind using 0.1 M NaOH solution for 24 hours. Adsorbents were characterized using Scanning Electron Miscroscopy (SEM) to determine the surface structure and particle size of the adsorbent. Furthermore, the adsorption process was carried out by contacting the adsorbent with lead solution based on the time difference of 10, 20 and 30 minutes and the adsorbent mass of 5, 10 and 15 grams. Based on the test results, the lowest concentration of lead was 1.692 and the highest concentration was 2.983. The most effective absorption of lead was at a level of 15 grams with a stirring time of 30 minutes with an absorption effectiveness of 83.30%.